Uncovering the Anti-Islamic Sentiment in The New Yorker Cover Issued on July 21, 2008: A Semiotic Analysis - Ahmad Sugianto; Rizki Denarti; Ilham Agung Prasetyo (Universitas Veteran Bangun Nusantara, 2021)
An image is deemed as one of the tools through which a magazine communicates particular messages. The messages may include various purposes, such as commercial or political purposes and values. Thereby, understanding a magazine cover image constitutes an essential issue for the underlying purposes and values that a magazine tries to communicate through it can be revealed. One of the most controversial magazine covers is that which was issued by The New Yorker on July 21, 2008, depicting Obama and his wife, Michelle. The portrayal was perceived as controversial on account of sentiment to a particular religion, namely Islam. Hence, this study aimed to figure out the meanings of the magazine cover, particularly in association with the anti-Islamic sentiment. Besides, the qualitative method, a semiotic analysis based on Barthes' (1986) theory of signification, were employed. The findings revealed that the signs had some indications for the anti-Islamic sentiment represented through the portrayals of the figures of Obama, Michelle, and the other pictures surrounding them. Moreover, some conclusions drawn from the analysis asserted that the magazine cover image represents signs having to do with the portrayal of Obama and Michelle during the election campaign and these also represents some attitudes vis-à-vis the anti-Islamic sentiment of some people in the US then. Finally, the present study advocates some considerations to reduce such a negative sentiment to Islam and Muslims, namely through education, appropriate and thorough framings from the American media, and intensive communication through inter-religious rapport and contact.